A Dual-Channel MAC Protocol with Fibonacci Backoff for Enhanced Efficiency in UAV-Based Sensor Networks - Owais Khan; Muhammad Ismail; Imad Ali (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Unmanned aerial vehicles (UAVs) are highly effective in collecting data from challenging environments equipped with Wireless Sensor Networks (WSNs), overcoming retrieval challenges. However, using a single-channel Medium Access Control (MAC) protocol for synchronization can lead to potential data collisions among multiple sensors sharing the same medium and result in high power consumption. In this article, we propose a dual-channel MAC protocol specifically designed for UAV-based data collection from WSNs. The protocol includes features such as varying transmission power levels for UAVs, dedicated channels for control and data packets, and a Fibonacci Backoff strategy. The UAV optimizes power usage by initially using low-power transmission and gradually increasing it. The dual-channel communication allows for separate channels for wakeup signals and data transmission, enhancing efficiency. Additionally, the sleep and wakeup mechanism conserves sensor node battery power during inactivity. We developed a discrete event simulator to evaluate the proposed protocol's performance. Our simulation results show that the average for each node count, the proposed protocol with the Fibonacci Backoff strategy improves network throughput by 20.68%, reduces delay by 22.32%, and decreases power consumption by 21.84% compared to the conventional Exponential Backoff method.